A Century of Progress: Reading Interventions for Students in Grades 4–12, 1914–2014. (September 2016) - Scammacca, Nancy K.; Roberts, Garrett J.; Cho, Eunsoo; Williams, Kelly J.; Roberts, Greg; Vaughn, Sharon R.; Carroll, Megan
The history of research on interventions for struggling readers in Grades 4 through 12 dates back to 19th-century case studies of seemingly intelligent children who were unable to learn to read. Physicians, psychologists, educators, and others were determined to help them. In the process, they launched a century of research on a wide variety of approaches to reading intervention. As shown in this systematic narrative review, much has changed over time in the conceptualization of reading interventions and the methods used to determine their efficacy in improving outcomes for struggling readers. Building on the knowledge gathered over the past 100 years, researchers and practitioners are well-poised to continue to make progress in developing and testing reading interventions over the next 100 years.